Constrictive Pericarditis in the Presence of Remaining Remnants of a Left Ventricular Assist Device in a Heart Transplanted Patient - R. Rivinius; M. Helmschrott; V. Koch; F. Sedaghat-Hamedani; P. Fortner; F. F. Darche; D. Thomas; A. Ruhparwar; B. Schmack; M. Karck; M. Akhavanpoor; C. Erbel; et al. (Case Reports in Transplantation)
Constrictive pericarditis (CP) is a severe subform of pericarditis with various causes and clinical findings. Here, we present the unique case of CP in the presence of remaining remnants of a left ventricular assist device (LVAD) in a heart transplanted patient. A 63-year-old man presented at the Heidelberg Heart Center outpatient clinic with progressive dyspnea, fatigue, and loss of physical capacity. Heart transplantation (HTX) was performed at another heart center four years ago and postoperative clinical course was unremarkable so far. Pharmacological cardiac magnetic resonance imaging (MRI) stress test was performed to exclude coronary ischemia. The test was negative but, accidentally, a foreign body located in the epicardial adipose tissue was found. The foreign body was identified as the inflow pump connection of an LVAD which was left behind after HTX. Echocardiography and cardiac catheterization confirmed the diagnosis of CP. Surgical removal was performed and the epicardial tubular structure with a diameter of 30 mm was carefully removed accompanied by pericardiectomy. No postoperative complications occurred and the patient recovered uneventfully with a rapid improvement of symptoms. On follow-up 3 and 6 months later, the patient reported about a stable clinical course with improved physical capacity and absence of dyspnea.